Learning Environment in Schools A Field Experience - Sharma, R.K.; Kamath, Asha K.V.D. (JOURNAL OF INDIAN EDUCATION, 2015)
There are several factors which influence the regularity and performance of learners in the school. Learning environment is one such factor which gives the experience of pleasure or pain, success or failure, active involvement or passive listening, to the students. The present study is an attempt to study the learning environment in Government Secondary Schools of Rajasthan, in terms of learner centeredness, learners’ hesitation in expressing themselves and learner treatment by the teacher. The study revealed that the classrooms are mainly teacher centered. Almost no activities are conducted for the learners or with the learners in the class. Teaching is highly oriented on textbook and classroom transaction is done with the textbooks in hand. Learners hesitate to participate in the teaching learning process because of abuse and punishment by the teachers for their wrong responses. Sometimes punishments are severe and highly de motivating. Teachers hardly respect the learners as individuals. Learners find it safe to non-participate in the class. Learners do not get sufficient time to think about the answer and their answers are not heard completely by the teachers. The present study is based on the field experience of the two authors in the secondary schools. The first author got an opportunity to perform field work in a government school for three months, while both the authors got the opportunity to observe classroom processes under one of the projects of NCERT. The experiences gained by them during field work and observation of classroom processes in relation to learning environment in those schools, is presented in this paper.